Pola Karakteristik NEET (Not In Employment, Education, Or Training) Dan Pengaruh Pengetahuan Pemuda Tentang Program Kartu Prakerja Terhadap Status NEET Di Masa Pandemi - Stephani Febryanna (Politeknik Statistika STIS, 2022)
Indonesia is experiencing population growth of productive age, and if it can pick well, this is a form of demographic bonus. However, in 2020, the NEET (Not in Education, Employment, or Training) number in Indonesia increased, even though in that year the government issued a Pre-Employment Card Program policy with the target population aged 18 years and over. NEET is divided into active NEET (in the labor force) and inactive NEET (not in the workforce). The proportion of NEET is more dominated by inactive NEET (not the workforce), the most significant percentage is in West Sulawesi Province, and the lowest is in DKI Jakarta Province. This study wanted to see the characteristic pattern of NEET youth and the influence of youth's knowledge about the existence of the Pre-Employment Card Program. The results of Cluster Analysis and Classification Analysis with Decision Tree, as well as logistic regression, namely NEET youth of female sex, marital status, low education, living in rural areas, and not knowing the Pre-Employment Card Program tend to be inactive NEET.